The role and mechanism of HMGB1-mediated Notch1/Hes-1 pathway in anxiety and depression-like behaviors in mice with chronic rhinosinusitis - Fangwei Zhou; Yiting Jiang; Yangsong Li; Jianyao Li; Tian Zhang; Guodong Yu (Molecular Medicine)
Abstract Background Chronic rhinosinusitis (CRS) is a global health issue, with some patients experiencing anxiety and depression-like symptoms. This study investigates the role of HMGB1 in anxiety and depression-like behaviors associated with the microglial Notch1/Hes-1 pathway in CRS mice. Methods A CRS mouse model was developed, and behavioral assessments were conducted to evaluate anxiety and depression-like behaviors. Techniques including 18F-FDG PET, Nissl staining, and immunofluorescence were used to assess hippocampal metabolic activity in CRS mice. Western Blot and RT-qPCR were employed to measure HMGB1 and Notch1/Hes-1 expression in the hippocampus, while ELISA determined inflammatory cytokine levels. The study also examined the effects of metformin on these behaviors and its mechanisms. Results CRS mice exhibited increased anxiety and depression-like behaviors, accompanied by enhanced hippocampal metabolic activity. HMGB1-siRNA treatment reduced these behaviors. Hippocampal glucose metabolism was markedly higher in CRS mice than in controls. Nissl staining revealed hippocampal neuron damage, and immunofluorescence indicated microglial activation in CRS mice. Reducing HMGB1 expression inhibited Notch1/Hes-1 pathway activation. In microglia, HMGB1 knockdown suppressed the Notch1/Hes-1 pathway, reducing inflammatory cytokine secretion. Metformin improved neuropsychiatric symptoms in CRS mice by inhibiting the Notch1/Hes-1 pathway after HMGB1 downregulation. Conclusion HMGB1 activates the microglial Notch1/Hes-1 pathway in CRS mice, promoting neuroinflammation and anxiety and depression-like behaviors. Metformin alleviates these effects.